Proximate analysis, phenolics, betalains, and antioxidant activities of three ecotypes of kaÑiwa (Chenopodium pallidicaule aellen) from peru - Huamaní F. (2020)
Kañihua (Chenopodium pallidicaule Aellen, Chenopodiaceae) is a native plant from the highlands of Peru and Bolivia that is characterized by its high nutritional value. It is considered a species of great genetic diversity and in this study we evaluated the nutritional characteristics, fatty acids profile, antioxidant compounds and antioxidant activities of three kañihua ecotypes from Peru named “Chilliwa” (light grey seeds), “Planta púrpura” (light orange seeds) and “Red kañiwa Condorsaya” (red seeds).